PEMBELAJARAN TARI KREASI LAMPUNG DENGAN KONSEP KREOGRAFI MELALUI MEDIA AUDIOVISUAL - I Wayan Jastra; muhammad fuad; susi wenhaningsih (Jurnal Seni dan Pembelajaran, 2016)
The aim this research was to observe the process and learning outcomes of Lampung creation dance with a choreography concept through audiovisual in extracurricular SMP Negeri 1 Banjar Margo Tulang Bawang. Observation, interview, documentation, testing practices, and non test used as data collection techniques of this study. In learning process of Lampung creation dance, through audiovisual media it was done by assessing three aspects such as creation of emotions that make the students are able to create six range of motions with different variation. On the appreciative of emotions, smile the looks so excessive, and the pattern of floor, the students are able to create seven of floor pattern, transition with the group.The results was showed the average value of 69 with enough category of sufficient